Isolation and Amino Acid Composition of Ribosomal Proteins from Bacillus stearothermophilus - Ansley, Steven B. (1969)
Twelve of the proteins from the 30S ribosome of Bacillus stearothermophilus were isolated by preparative disc electrophoresis. Amino acid analyses of these proteins showed them to be different from each other. The gross amino acid composition of 30S ribosomal protein from B. stearothermophilus and Escherichia coli are virtually identical. A number of the proteins of B. stearothermophilus had electrophoretic mobilities similar or identical to 30S ribosomal proteins of E. coli. However, there was little similarity between the two organisms in amino acid composition of individual proteins. There were no unusual chemical features of the B. stearothermophilus proteins which could explain the relative thermal stability of this organism's ribosomes.